Endovascular treatment of intracranial infectious aneurysms in eloquent cortex with super-selective provocative testing: Case series and literature review. Issue 2 (April 2016) - Fusco, Matthew R; Stapleton, Christopher J; Griessenauer, Christoph J; Thomas, Ajith J; Ogilvy, Christopher S
Intracranial infectious aneurysms (IIAs) are a rare subgroup of intracranial aneurysms. Often erroneously termed mycotic aneurysms, these lesions most often result from infectious endocarditis and involve the distal anterior cortical circulation. Diagnosis typically follows headaches or septic infarcts, although increasing numbers of lesions are found incidentally, during screening protocols for infectious endocarditis. Open surgical treatment was previously the mainstay of treatment; however, these IIAs are often fusiform and quite fragile, making open surgical obliteration difficult and typically requiring lesion trapping. Current treatment techniques more commonly involve endovascular coil embolization or parent vessel occlusion. Many of these lesions occur distally, in or around the eloquent cortex, making embolization potentially dangerous. We present cases that highlight the use of super-selective provocative testing with sodium amobarbital and lidocaine, to help clarify and predict the risk of parent vessel occlusion in IIAs located in the eloquent cortex.